Anatomy, Flow Cytometry, and X-Ray Tomography Reveal Tissue Organization and Ploidy Distribution in Long-Term In Vitro Cultures of Melocactus Species - Torres-Silva, Gabriela; Matos, Elyabe Monteiro; Correia, Ludmila Freitas; Fortini, Evandro Alexandre; Soares, Wellington Santos; Batista, Diego Silva; Otoni, Caio Gomide; Azevedo, Aristéa Alves; Viccini, Lyderson Facio; Koehler, Andréa Dias; Resende, Sheila Vitória; Specht, Chelsea Dvorak; et al. (Frontiers in Plant Science, 2020)
Cacti have a highly specialized stem (cladode) that enables survival during extended dry periods. Despite the ornamental value of cacti and the fact that cladodes represent the main source of explants in tissue culture, there are no studies on their morpho-anatomical and cytological characteristics in Melocactus. The present study sought to address the occurrence of cells with mixed ploidy in cacti tissues and morphological alterations during in vitro shoot production. Specifically, it aimed to understand how the Melocactus cladode tissue was organized, and how mixoploidy was distributed if it was mixoploid, and whether the pattern of ploidy changed after long periods of in vitro culture. To analyze tissue organization, Melocactus glaucescens and Melocactus paucispinus plants germinated and cultivated in vitro were analyzed by toluidine blue, Xylidine Ponceau, Periodic Acid Schiff, ruthenium red, and acid floroglucin. To investigate the tissue ploidy pattern, samples of topophysical longitudinal (apical, medial, and basal) and radial (periphery, cortex, stele, and root apexes) zones of the cladode from four- and ten-year in vitro cultures were analyzed by flow cytometry. X-ray micro-computed tomography was performed with fragments of cladodes from both species. The scarcity of support elements (i.e., sclereids and fibers) indicates that epidermis, hypoderm, wide-band tracheids present on vascular bundles and stele, as well as the water stored in aquifer parenchyma cells along the cortex provide physical support to the cladode. Parenchyma cells increase in volume, along with a five-fold rise in ploidy. M. glaucescens and M. paucispinus exhibit the same pattern of cell ploidy irrespective of topophysical region or age, but differ in ploidy between cladode periphery, cortex, stele, and roots. Mixoploidy in Melocactus is not related to the age of the culture, but is a developmental trait, whereby endocycles promote cell differentiation to accumulate valuable water.